Muscarinic and Nicotinic Modulation of Memory but not Verbal Problem-solving - Smyth, Shawn F. (Cogn Behav Neurol, 2019)
Aspects of cognitive flexibility are modulated by the noradrenergic system, which is important in arousal and attention. Acetylcholine also modulates arousal and attention, as well as working memory. Effects of muscarinic and nicotinic antagonism on memory are well established. Our purpose was to test whether muscarinic and nicotinic antagonism affect aspects of cognitive flexibility, specifically verbal problem-solving, as well as memory, given acetylcholine’s role in attention and arousal. Eighteen participants attended three testing sessions. Two hours before testing, participants received either 0.6 mg scopolamine, 10 mg mecamylamine, or placebo. Then, participants were tested on three memory tasks (Buschke Selective Reminding Test [BSRT], California Verbal Learning Test [CVLT], Rey Complex Figure Test), two verbal problem-solving/cognitive flexibility tasks (Compound Remote Associates Test, a timed anagram test), and a spatial inductive reasoning task (Raven’s Progressive Matrices). Task order and drug order were counterbalanced. Memory impairment in memory was seen on one BSRT measure and multiple CVLT measures with scopolamine and with one BSRT measure with mecamylamine. There were no effects of either drug on any of the tasks involving cognitive flexibility, including verbal problem-solving. Specific memory impairments were detected using muscarinic, and to a marginal extent, nicotinic antagonists, as expected, but no effect was seen on cognitive flexibility. Therefore, although both the noradrenergic and cholinergic systems play important roles in arousal and cortical signal-to-noise processing, the cholinergic system does not appear to have the same effect as the noradrenergic system on cognitive flexibility, including verbal problem-solving.